THE IMPACT OF INTANGIBLE ASSET AND RESEARCH AND DEVELOPMENT ON FIRM VALUE - Jacqueline, Jacqueline; Luky Patricia Widianingsih; Anastasia Filiana Ismawati (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
In the era of globalization, advances in science and developments in information technology encourage the world’s economic growth. New forms and methods of economic activities, such as e-commerce, are born. As a technology-based industry, e-commerce is assessed by its intangible assets. The sustainability of this sector is proven by its research and development activities. In recent years, China has become the country that dominates the world’s e-commerce market. Now, e-commerce is one of the industries highlighted by investors in the trading world. This research aims to analyze the effect of intangible assets and research and developments on Chinese e-commerce firm value. The samples used in this study were 17 Chinese e-commerce companies listed on the 3 largest United States Stock Exchanges, namely NASDAQ, NYSE and NYSE American during the 2014- 2019 period. Data collection uses secondary data derived from each annual report. The analysis was conducted using multiple regression supported by SPSS version 22. This study showed that intangible assets and research and development positively affected firm value. The result indicates that both intangible assets and research and development have a positive effect on firm value.